2014
DOI: 10.1021/jf500107j
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin Metabolites Are Abundant and Persistent in Human Urine

Abstract: LC-MS/MS revealed that metabolites of anthocyanins (Acn) were abundant in human urine (n = 17) even after 5 days with no dietary Acn. After intake of 250 mL of blueberry juice, parent Acn were 4% and Acn metabolites were 96% of the total urinary Acn for the following 24 h. Multiple reaction monitoring revealed 226 combinations of mass transition × retention times for known Acn and predicted Acn metabolites. These were dominated by aglycones, especially aglycone glucuronides. The diversity of Acn metabolites co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
93
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(99 citation statements)
references
References 36 publications
4
93
0
1
Order By: Relevance
“…Furthermore, Kalt and colleagues reported similar results. After the ingestion of blueberry juice, which did not contain any detectable pelargonidin glycosides, significant amounts of pelargonidin based metabolites could be detected in the urine of 17 study subjects [66]. The described interconversion of anthocyanins due to xenobiotic and bacterial metabolism was suggested by these authors.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Furthermore, Kalt and colleagues reported similar results. After the ingestion of blueberry juice, which did not contain any detectable pelargonidin glycosides, significant amounts of pelargonidin based metabolites could be detected in the urine of 17 study subjects [66]. The described interconversion of anthocyanins due to xenobiotic and bacterial metabolism was suggested by these authors.…”
mentioning
confidence: 84%
“…This includes addition and removal of methyl and hydroxyl groups (pelargonidin is lacking of one hydroxyl group compared to cyanidin) [66]. Furthermore, Kalt and colleagues reported similar results.…”
mentioning
confidence: 86%
“…The most recent papers published on the subject are summarized in Table 2 [96,101,[140][141][142][143][144][145][146][147][148][149][150][151]. Anthocyanins are metabolized to a structurally diverse range of metabolites that exhibit dynamic kinetic profiles.…”
Section: Flavonoids -From Biosynthesis To Human Health 212mentioning
confidence: 99%
“…Pharmacokinetic trial to evaluate the bioavailability of anthocyanins and colonic polyphenol metabolites after consumption of aronia berry extract in plasma and urine [96] Evaluation of the protective effects of protocatechuic acid [140] Effects of black raspberry extract and protocatechuic acid on DNA adduct formation and mutagenesis in rat oral fibroblasts [141] Influence of ethanol on the bioavailability and pharmacokinetics of blackberry anthocyanins [142] Pharmacokinetic trial to evaluate the of nanoencapsulation of a phenol extract from grape pomace on human plasma [143] Pharmacokinetic characterization of anthocyanins in overweight adults on the basis of meal timing [97] Determination of cyanidin 3-glucoside in rat brain, liver and kidneys: a short-term pharmacokinetic study [144] Pharmacokinetics, bioavailability and regional brain distribution of polyphenols from apple-grape seed extract mixture and bilberry extract [145] Evaluation of changes in metabolic parameters, and in cardiovascular and liver structure and function in rat due to administration of either cyanidin 3-glucoside or Queen Garnet plum juice [146] Bioavailability and uptake of anthocyanins and their metabolites from an anthocyanins-rich grape/ blueberry juice and smoothie in vivo and in vitro [101] Effects of anthocyanins and their corresponding anthocyanidins on the expression levels of organic anion transporting polypeptides in primary human hepatocytes [147] Effect of flavan-3-ols and anthocyanins against inflammatory-related diseases [148] Anthocyanin pharmacokinetics and dose-dependent plasma antioxidant pharmacodynamics by intake of Montmorency tart cherries in healthy humans [149] Pharmacokinetics of the metabolites of cyanidin-3-glucoside [150] Abundance and persistence of metabolites of anthocyanins in human urine [151] …”
Section: Comments Referencesmentioning
confidence: 99%
“…Accurate determination of bioavailability of phenolic compounds remains yet a challenge due to the presence of enterohepatic circulation, distribution to various tissues, chemical binding to other components, low stability of some metabolites and technical difficulties in detecting certain metabolites. In a recent research, anthocyanin metabolites could be found in urine in fairly large quantities even after days from consumption [54].…”
Section: Bioavailability and Gut Healthmentioning
confidence: 98%